Influence of Leadership Style, Team Attachment, and Teamwork on the Performance of the Regional Election Winning Team in Indonesia: Research on the Indonesian Independent Farmers Organization of Central Java Province - Dyah Ayu Syukma Pertiwi1; Helmi Haris (Admisi dan Bisnis, 2025)
This study aims to analyze the influence of leadership style, team involvement, and teamwork on the performance of election campaign teams in Indonesia, especially within the Independent Indonesian Farmers organization in Central Java Province. The methodology used is a quantitative approach using purposive sampling techniques, involving 60 respondents as a sample. Data was collected through a Likert scale-based questionnaire to measure respondents' perceptions of the variables studied. Data analysis was carried out using SPSS software, by testing validity, reliability, normality, heteroscedasticity, and applying multiple regression analysis, F test, and T test. The implications of these findings provide strategic insights for the Independent Indonesia Farmers organization to improve the effectiveness of election campaign teams by strengthening effective leadership practices, increasing active involvement of team members in every stage of the campaign, and promoting collaborative synergy among team members to optimally achieve common goals. This research makes an important contribution in the context of election campaign management at the organizational level, by highlighting the importance of internal factors such as leadership and teamwork in achieving expected performance. The next step could involve developing more specific strategies and training programs to reinforce aspects that have been identified as key to success in the context of an election campaign.   Penelitian ini bertujuan untuk menganalisis pengaruh gaya kepemimpinan, keterlibatan tim, dan kerja tim terhadap kinerja tim kampanye pemilu di Indonesia, khususnya di dalam organisasi Petani Indonesia Mandiri Provinsi Jawa Tengah. Metodologi yang digunakan adalah pendekatan kuantitatif menggunakan teknik purposive sampling, melibatkan 60 responden sebagai sampel. Data dikumpulkan melalui kuesioner berbasis skala Likert untuk mengukur persepsi responden terhadap variabel yang diteliti. Analisis data dilakukan dengan menggunakan software SPSS, dengan menguji validitas, keandalan, normalitas, heteroscedastisitas, dan menerapkan analisis regresi berganda, uji F, dan uji T. Implikasi dari temuan ini memberikan wawasan strategis bagi organisasi Petani Indonesia Mandiri untuk meningkatkan efektivitas tim kampanye pemilu dengan memperkuat praktik kepemimpinan yang efektif, meningkatkan keterlibatan aktif anggota tim di setiap tahap kampanye.  dan mempromosikan sinergi kolaboratif antar anggota tim untuk mencapai tujuan bersama yang optimal. Penelitian ini memberikan kontribusi penting dalam konteks pengelolaan kampanye pemilu di tingkat organisasi, dengan menyoroti pentingnya faktor internal seperti kepemimpinan dan kerja tim dalam mencapai kinerja yang diharapkan. Langkah selanjutnya mungkin melibatkan pengembangan strategi dan program pelatihan yang lebih spesifik untuk memperkuat aspek yang telah diidentifikasi sebagai kunci keberhasilan dalam konteks kampanye pemilu